Outcome of Teenage Pregnancy - Tripathi, M; Sherchand, A (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Teenage pregnancy is coming up as one of the most important social and public health problem all over the world. Teenage pregnancy is a common social phenomenon with public health and medical consequences worldwide. The study was done to compare obstetric and perinatal outcome in teenage and non-teenage pregnancies. METHODS: This is a comparative study. The study duration was from 10th January 2010 to 9th January 2012. All teenage mothers (aged 13-19 completed years at delivery) delivering in the Gandaki Medical College (GMC) hospital, Pokhara were taken as cases (study group). Next 2 consecutive deliveries in the age group of 20-30 year were selected as control for each case. RESULTS: The incidence of complications in teenage primigravida (study group) compared with non-teenage (control group) deliveries were anemia (20% vs 6%), preterm labour (20 % vs 7%), Urinary tract infection(UTI) (8 % vs 4%), pre-eclampsia (4 % vs 2%) and Prelabour Rupture of Membrane(PROM) (10% vs 4%). Similarly, abnormal presentation (6% vs 2%), placenta praevia (4% vs 1%), Fetal distress(FD) (8% vs 3%), Cephalo Pelvic Disproportion(CPD) (6 % vs 2%) and Low Birth Weight(LBW) (24 % vs 9 %)were recorded respectively. In study group, 58% of the patients were delivered vaginally & 24% were delivered by caesarean section, 6% delivered by breech and 12% of patients had instrumental delivery. In non-teenage group, 74% of the patients delivered vaginally & 14% were delivered by caesarean section, 4% delivered by breech and 8% of patient had instrumental delivery. CONCLUSION: Teenage pregnant mothers had high rate of inadequate prenatal care, suffered more from anemia, UTI, & were more likely to deliver preterm and had low birth weight babies. They had high rates of operative and instrumental delivery. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11168 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 11-14